Effects of postactivation potentiation on mechanical output and muscle architecture during electrically induced contractions in plantar flexors - Bourgeois, H.; Duchateau, J.; Baudry, S. (Journal of Applied Physiology, 2022)
This study investigated the effects of postactivation potentiation (PAP) on the force output and muscle architecture in plantar flexor muscles. The mechanical response to a single electrical stimulus (twitch) and to two (doublet) and three (triplet) stimuli (10-ms interpulse interval) was measured before and after a 6-s maximal voluntary contraction (MVC). Ultrasound imaging was used to measure fascicle length and pennation angle of the gastrocnemius medialis at rest and during the electrically induced contractions. Immediately after the conditioning MVC, twitch peak force (+40%) and its maximal rate of force development (+57%) and relaxation (+62%) were greater than before the MVC (P < 0.001). The PAP extent was less for the doublet than for the twitch and for the triplet than for the doublet (P < 0.05). Whereas none of the architectural parameters changed at rest, fascicle shortening and increase in pennation angle during contractions were greater after than before the conditioning MVC, with a greater extent (P < 0.001) during the twitch (+28% and +58%, respectively) compared with the doublet (+16% and +36%) and the triplet (+12% and +14%). Overall, our results indicate that the effect of the conditioning MVC on mechanical output and muscle architecture decreased from the twitch to the triplet in plantar flexor muscles. The decreased PAP observed during doublet and triplet compared with twitch indicates that the benefit of this mechanism to the enhancement of muscle performance becomes progressively less effective during successive muscle activation.